STRATEGIC DIMENSIONS OF RUSSIAN LANGUAGE LISTENING TRAINING IN THE CHINESE AUDIENCE - Daver, M. V. (Викладання мов у вищих навчальних закладах освіти на сучасному етапі. Міжпредметні зв’язки, 2014)
Strategic dimensions are a fundamental requirement on modern linguistic education as well as computer-assisted listening training that has different aspects related to the acquisition of new competences. Strategic competence in language learning is not always considered as a separate component of the communicative competence as it involves several sub-levels in accordance with the needs of target audience. The development of the Chinese university students’ initial strategic competence due to the previous communicative experience, when learning a new language in a computer-assisted foreign language classroom, has been investigated in the article.